Effect of Anti-Programmed Cell Death-1 Antibody on Middle Ear Mucosal Immune Response to Intranasal Administration of Haemophilus influenzae Outer Membrane Protein - Kazuhiro Yoshinaga; Takashi Hirano; Shingo Umemoto; Yoshinori Kadowaki; Takayuki Matsunaga; Masashi Suzuki (Vaccines)
Background/Objectives: Acute otitis media is a common pediatric infection caused primarily by nontypeable Haemophilus influenzae. With rising antibiotic resistance, vaccines are essential for combating this public health issue. Although the PD-1/PD-L1 pathway has been extensively studied for its role in tumor immunity, its impact on mucosal immunity, particularly in vaccine responses, is unclear. Methods: BALB/c mice were intranasally immunized with nontypeable H. influenzae outer membrane protein and treated with anti-PD-L1 antibodies. Immune responses were evaluated in middle ear mucosa (MEM), the cervical lymph node, and the spleen using an enzyme-linked immunosorbent assay, an enzyme-linked immunospot assay, and flow cytometry. The effects on CD4+ T cells, T follicular helper (Tfh) cells, and B-cell differentiation were analyzed. Results: Anti-PD-L1 antibody treatment increased CD3+CD4+CD185+ (CXCR5+) Tfh cells in MEM, which play a crucial role in supporting B-cell activation and antibody production. This correlated with a significant increase in IgA- and IgG-producing cells in MEM, which enhanced local bacterial clearance. Although B-cell activation and differentiation into plasmablasts were observed in MEM, no significant changes were noted in the cervical lymph node and spleen, suggesting a localized enhancement of mucosal immunity. Conclusions: Anti-PD-L1 antibodies promoted Tfh cell expansion and B-cell differentiation in MEM, leading to enhanced antibody production and improved bacterial clearance. These findings suggest that PD-L1 blockade can potentiate mucosal vaccine-induced immunity by strengthening local humoral responses. This supports its potential application in developing intranasal vaccines for acute otitis media.